Animal Models of Multiple Sclerosis. Issue 6 (25th June 2021) - Smith, Paul
Abstract: Animal models with high translational validity are essential tools in understanding disease pathogenesis and in the development of therapeutic strategies. Multiple sclerosis (MS) is an autoimmune demyelinating disease of the central nervous system characterized by progressive neurological deficits and socioeconomic burden. Experimental autoimmune encephalomyelitis (EAE) is the most extensively utilized animal model of MS, with well‐characterized rodent and non‐human primate variants. The EAE model is typically induced by either active immunization with myelin‐derived proteins or peptides in adjuvant or by passive transfer of activated myelin‐specific CD4 + T lymphocytes. To date, the EAE model has been an essential tool in the development of at least seven U.S. Food and Drug Administration (FDA)−approved immunomodulatory drugs for the treatment of MS, including glatiramer acetate, fingolimod, and natalizumab. However, the translational validity of the EAE model is frequently compromised due to poor study design, inconsistent clinical scoring endpoints, and inappropriate statistical calculations. No single animal model accurately reflects the complexity of human MS pathogenesis. Beyond EAE, multiple additional animal models are described, including Theiler's murine encephalomyelitis virus and cuprizone‐induced demyelination, which facilitate the study of pathogen‐induced CNS autoimmunity and remyelination, respectively. This overview summarizes several of the most frequently used animal models of MS and highlights key factors that significantly influence the experimental outcome and affect translational validity. © 2021 Wiley Periodicals LLC.